ATRT-17. TARGETING GLUTAMINE METABOLISM LOWERS METHYLATION POTENCIALS IN AT/RT AND SYNERGIZE WITH TAZEMETOSTAT. (4th December 2020) - Nakata, Satoshi; Wang, Sabrina; Alt, Jesse; Slusher, Barbara; Eberhart, Charles; Raabe, Eric; Rubens, Jeffrey
Abstract: Atypical teratoid/rhabdoid tumors (AT/RT) have a single recurring genetic mutation in SMARCB1 . This deletion leads to an abnormal SWI/SNF chromatin remodeling complex and the constitutive activation of EZH2 . S-adenosyl-L-methionine (SAM) donates a methyl group to EZH2 which then methylates DNA and histones leading to the abnormal gene expression responsible for AT/RT's aggressive phenotype. We have previously shown that glutamine metabolic inhibition with 6-diazo-5-oxo-L-norleucine (DON) confers a survival advantage in AT/RT. In this study, we identified with ultra-high performance liquid chromatography mass spectrometry that DON treatment lowered the methylation potential in AT/RT (Decreased SAM:SAH ratio, t-test in 5 AT/RT human-derived cell models comparing DON treatment to DMSO control, p<0.05). AT/RT cell lines grown in glutamine deplete media compared to normal growth conditions also had a reduced methylation potential (decreased SAM:SAH, t-test, p<0.05). DON treatment over 5 days decreased histone methylation (as determined by western blot for H3K27me3). Tazemetostat is a small molecule inhibitor that blocks the SAM methyl donor site on EZH2. We find that DON combines synergistically with Tazemetostat to slow AT/RT cell growth (MTS assay, p<0.01 t-test; MUSE viability assay, p<0.01 ANOVA) and enhances cytotoxicity (MUSE Annexin-V, p<0.01 by ANOVA). Synergies were especially pronounced at low concentrations of Tazemetostat which is significant given that Tazemetostat's efficacy in AT/RT has been limited by poor CNS penetration. These studies identify a novel treatment strategy that has potential to improve survival in AT/RT.